2022
DOI: 10.3389/fnins.2022.947240
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbes and food reward: From the gut to the brain

Abstract: Inappropriate food intake behavior is one of the main drivers for fat mass development leading to obesity. Importantly the gut microbiota-mediated signals have emerged as key actors regulating food intake acting mainly on the hypothalamus, and thereby controlling hunger or satiety/satiation feelings. However, food intake is also controlled by the hedonic and reward systems leading to food intake based on pleasure (i.e., non-homeostatic control of food intake). This review focus on both the homeostatic and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 215 publications
0
12
0
Order By: Relevance
“…SCFA can be associated with GPR41 and directly regulate the sympathetic nervous system ( 12 ). In recent years, interest in the “microbiota-gut-brain axis” has emerged, in which gut microbiota metabolites play an important mediating role ( 5 ). Based on the study of gut microbiota in patients with cardiovascular disease, Yu et al proposed a “gut-brain-heart” axis, through which SCFA may be involved in cardiovascular regulation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFA can be associated with GPR41 and directly regulate the sympathetic nervous system ( 12 ). In recent years, interest in the “microbiota-gut-brain axis” has emerged, in which gut microbiota metabolites play an important mediating role ( 5 ). Based on the study of gut microbiota in patients with cardiovascular disease, Yu et al proposed a “gut-brain-heart” axis, through which SCFA may be involved in cardiovascular regulation ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the close relationships between the microbiome and human diseases have been demonstrated, and studies have confirmed that gut microbiota are associated with extraintestinal diseases, such as liver-, brain-, and immunity-related conditions (3)(4)(5). The digestive tract is directly connected to the outside environment and contains up to 100 trillion microorganisms, mainly in the colon (6).…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota can also influence host metabolic phenotypes by inversely affecting appetite and dietary preferences. [315][316][317] Thus, the benefits of dietary patterns on cardiometabolism may be far greater than we thought, even beyond genetic and environmental factors, as shown in Figure 4.…”
Section: Gut Microbiota and Its Metabolitesmentioning
confidence: 82%
“…From the above review of recent evidence, it is easy to conclude that dietary patterns can participate in various aspects of metabolic regulation by shaping the gut microbiome, as shown in Table S3. Gut microbiota can also influence host metabolic phenotypes by inversely affecting appetite and dietary preferences 315–317 . Thus, the benefits of dietary patterns on cardiometabolism may be far greater than we thought, even beyond genetic and environmental factors, as shown in Figure 4.…”
Section: Potential Mechanism Mediating the Effects Of Dietary Patternsmentioning
confidence: 90%
“…The gut microbiota, which consists of trillions of microorganisms, is a vast and complicated system often referred to as a "hidden organ" that plays a crucial role in regulating host lipid metabolism and is implicated in meat quality [9][10][11]. The interplay between the gut microbiota and host metabolism has attracted attention in the research community focused on lipid metabolic disorders and related diseases.…”
Section: Introductionmentioning
confidence: 99%